Guinea-Bissau : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
A major element of the persistent fiscal imbalances in Guinea-Bissau is the relatively low level of revenue compared with other sub-Saharan African (SSA) countries. Fiscal revenues, including grants, trended downward significantly in Guinea-Bissau from 1991 through 2005, especially during the last five years. Nontax revenues are stagnant as a proportion of GDP as a result of weak fisheries administration and control. Tax revenues as a proportion of GDP are relatively low in Guinea-Bissau even compared with other low-income countries.